Ecological Construction of Religious Resilience among Islamic Education Students Facing Quarter-Life Crisis: A Comparative Case Study of Public and State Islamic Campus Ecologies - Marwal Blantara Susetyo; Wawan Hermawan; Cucu Surahman (Ta'dibuna: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (IRE/PAI) students are highly vulnerable to quarter-life crises amidst intense social expectations of piety. This study aims to analyze and compare the construction of PAI students' religious resilience in navigating this crisis at Universitas Pendidikan Indonesia (UPI) and UIN Sunan Gunung Djati Bandung. A qualitative comparative case study design was applied to eight purposively selected informants, four at each site, in their fifth and seventh semesters, through indepth interviews, ecological observation, and document analysis, followed by intra- and cross-case analysis. Findings reveal that the heterogeneous general university ecology of UPI fosters flexible and independent resilience, supported by restorative physical spaces. Conversely, the religioncentred state Islamic university ecosystem of UIN offers strong structural support but carries risks of social-moral pressure due to standardized communal piety. This study concludes that religious resilience is not an innate attribute (given trait), but rather a systemic construction significantly shaped by the campus ecosystem (ecological construction of religious resilience)